Studi Komparatif Peran Notaris dan Pejabat Pembuat Akta Tanah (PPAT) dalam Pembuatan Akta Jual Beli - Pratama, Fadhli Nur; Ana Silviana (UNES Law Review, 2024)
This research aims to analyze and compare the roles of notaries and land deed officials in making sale and purchase deeds, as well as identify problems and challenges faced in practice. This research uses a normative juridical approach method that seeks to synchronize legal provisions against norms, and other legal regulations that have a relationship with the application of legal regulations in the field with literature study data collection techniques. The results show that there is an overlap of authority between notaries and PPATs that can cause confusion in the community in choosing the appropriate service. Differences in procedures and operational standards between these two professions also affect the efficiency and legal certainty in making sale and purchase deeds. In addition, limited public understanding of the role of each profession results in inappropriate service selection and potential legal disputes in the future. Bureaucratic constraints, regulatory changes, and technical land issues are significant challenges faced by notaries and PPATs in carrying out their duties. This research emphasizes the importance of education and socialization regarding the roles and authorities of notaries and PPATs, as well as regulatory reforms to reduce overlapping authorities and improve the efficiency of the sale and purchase deed process. With better understanding and better coordination between notaries, PPATs, and related institutions, it is expected that legal certainty and rights protection in property sale and purchase transactions can be improved.